2017
DOI: 10.1037/ccp0000230
|View full text |Cite
|
Sign up to set email alerts
|

Remotely delivering real-time parent training to the home: An initial randomized trial of Internet-delivered parent–child interaction therapy (I-PCIT).

Abstract: Findings build on the small but growing literature supporting the promising role of new technologies for expanding the delivery of behavioral parent training. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
157
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(181 citation statements)
references
References 32 publications
11
157
0
4
Order By: Relevance
“…For these and other reasons, telepsychiatry has increased in prominence as a vehicle for individual and group treatment. Another study (Comer et al, 2017) found internet-delivered PCIT (I-PCIT) to be more effective than clinic based PCIT for 3-5 year olds with disruptive behavior disorders both at post-treatment (treatment response: 70% and 55%, respectively) and 6-month follow-up (55% and 40%, respectively); however, ADHD symptoms/diagnoses were not assessed. Findings indicated significant improvements in mother-rated ADHD symptoms, defiance/aggression, and social functioning as well as teacher-rated prosocial behavior.…”
Section: Barriers To Carementioning
confidence: 99%
“…For these and other reasons, telepsychiatry has increased in prominence as a vehicle for individual and group treatment. Another study (Comer et al, 2017) found internet-delivered PCIT (I-PCIT) to be more effective than clinic based PCIT for 3-5 year olds with disruptive behavior disorders both at post-treatment (treatment response: 70% and 55%, respectively) and 6-month follow-up (55% and 40%, respectively); however, ADHD symptoms/diagnoses were not assessed. Findings indicated significant improvements in mother-rated ADHD symptoms, defiance/aggression, and social functioning as well as teacher-rated prosocial behavior.…”
Section: Barriers To Carementioning
confidence: 99%
“…Auch bezüglich Elterntrainings gibt es erste Evidenz für erfolgreiche Online-Verfahren. Die Untersuchung der internetbasierten Parent-Child Interaction Therapy (PCIT) im Vergleich mit der klinischen PCIT [12] zeigt, dass ein Training via Webcams und Bluetooth-Kopfhörern für die Eltern und Kinder gleichermaßen profitabel ist. Bezüglich wahrgenommener Barrieren zur Durchführung des Trainings wurde die internetbasierte Version von den Eltern sogar besser bewertet.…”
Section: Wirksamkeit Onlineunclassified
“…Parent involvement in intervention has repeatedly been associated with benefits such as increased opportunities for learning, as well as positive generalization and maintenance outcomes (Dogan et al, ; Heitzmann‐Powell, Buzhardt, Rusinko, & Miller, ). Involving parents in intervention can benefit children, parents, and practitioners by saving time and resources (Dogan et al, ), and can overcome some of the barriers that restrict access to intervention for families (e.g., cost, availability, accessibility; Comer et al, ; Heitzmann‐Powell et al, ).…”
mentioning
confidence: 99%